Strategic design of agricultural financing in rural area based on competitiveness of BMT - Adistiar Prayoga (Journal of halal product and research (JPHR), 2018)
The existence of Baitul Maal wat Tamwil (BMT) in East Java is expected to be an alternative in capital problem, especially on micro / small farm in rural East Java. The role of BMTs can be analyzed based on the internal and external conditions of BMT institutions that perform structural functions as financial service cooperatives and cultural functions as social institutions in the redistribution of Islamic wealth. This study used a mixed case study method with descriptive analysis. Field studies were conducted in November 2016-February 2017 in Surabaya, Tulung Agung, Pasuruan, and Gresik in East Java using primary and secondary data. Secondary data sourced from BMT financial report during 2013-2015. Further analysis of internal and external BMT conditions through Focus Group Discussion (FGD). The result of institutional analysis, mention that healthy institution and competitiveness to channel agriculture financing both structurally and culturally. The BMT management response to the internal and external environment is in the position of being (average). Analysis of EFE (External Factor Evaluation) and IFE (Internal Factor Evaluation) is possible for the institution to combine growth strategies (grow) and development (build). The recommended of alternative institutional strategy to BMT in agricultural financing in rural East Java is market penetration and product development.